Influence of an Interventional Health Education in Enhancing the Perceived Learning Needs of Patients with Myocardial Infarction - Zainab Kadhim Hussein, Widad K. Mohammed, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Myocardial infarction is the leading cause of coronary heart disease and death. Because post-MI patients are more likely to have another attack, it is vital that they have enough knowledge about their health and the appropriate self-care. post-MI patients, it is critical for post-MI patients to have adequate health information and self-care, especially if they have risk factors such as smoking, hypertension, hyperlipidemia, obesity, and a lack of exercise. Objectives: To evaluate influence of an interventional health education in enhancing the perceived learning needs of patients with myocardial infarction. Methods: A quasi-experimental design was used with the application of pre and post-test approach for both studied and controlled groups. This study was conducted at cardiac advisory department on purposive sample was selected to obtain representative and accurate data consisting of (90) patients at Missan Center for Cardiac Diseases and Surgery, (10) patients were excluded for the pilot study. Data were analyzed using descriptive statistical data analysis approach of frequency, percentage, mean, mean of scores, a total of scores, range and standard deviation and inferential statistical data analysis approach T-test, and analysis of variance (ANOVA). Results: highly significant difference between pre and posttests responses at (P value < .05) in the study group related to all domains of the study. Conclusions: Less than one-quarter of patients in the study group were institute graduate level, and more than one-quarter of patients in the control group were secondary level graduate, one quarter of patients in the study group were within employee level; and more than one quarters in control group were within the retired level. more than half of patients in the study group and more than two-thirds of patients in the control group were married. In pretest and posttest, there is a significant influence of an interventional health education in enhancing the perceived learning needs of patients with myocardial infarction. Recommendations: The study recommend that it is critical to update patient learning needs by encouraging and inspiring patients to participate in particular interventional health education on the perceived learning needs of patients with Myocardial Infarction. Patients should have access to continued education and resources that enhance patient's learning needs during their hospitalization.